An overview of 25 years of incidence, treatment and outcome of colorectal cancer patients. Issue 11 (29th September 2018) - Brouwer, Nelleke P.M.; Bos, Amanda C.R.K.; Lemmens, Valery E.P.P.; Tanis, Pieter J.; Hugen, Niek; Nagtegaal, Iris D.; de Wilt, Johannes H.W.; Verhoeven, Rob H.A.
Abstract : Regarding the continuous changes in the diagnostic process and treatment of colorectal cancer (CRC), it is important to evaluate long‐term trends which are relevant in giving direction for further research and innovations in cancer patient care. The aim of this study was to analyze developments in incidence, treatment and survival for patients diagnosed with CRC in the Netherlands. For this population‐based retrospective cohort study, all patients diagnosed with CRC between 1989 and 2014 in the Netherlands were identified using data of the nationwide population‐based Netherlands Cancer Registry ( n = 267, 765), with follow‐up until January 1, 2016. Analyses were performed for trends in incidence, mortality, stage distribution, treatment and relative survival measured from the time of diagnosis. The incidence of both colon and rectal cancer has risen. The use of postoperative chemotherapy for Stage III colon cancer increased (14–60%), as well as the use of preoperative (chemo)radiotherapy for rectal cancer (2–66%). The administration of systemic therapy and metastasectomy increased for Stage IV disease patients. The 5‐year relative survival increased significantly from 53 to 62% for colon cancer and from 51 to 65% for rectal cancer. Ongoing advancements in treatment, and also improvement in other factors in the care of CRC patients—such as diagnostics, dedicated surgery and pre‐ and postoperative care—lead to a continuous improvement in the relative survival of CRC patients. The increasing incidence of CRC favors the implementation of the screening program, of which the effects should be monitored closely. Abstract : What's new? To best inform new directions for cancer management, it's important to study historical trends. Here, the authors analyzed 25 years of data in The Netherlands on colorectal cancer incidence, treatment and survival. During the period from 1989 to 2014, both incidence and 5‐year relative survival increased. Certain treatments also became more common, such as postoperative chemotherapy for Stage III patients and systemic therapy and surgical removal of metastases for Stage IV patients. Improved diagnostics and treatments have helped more patients survive, and the rising incidence of CRC supports the use of the nationwide screening program, introduced by the Dutch government in 2014.